Halal Certification Challenges for Javanese Muslim Entrepreneurs in a Phenomenological Perspective - Masyhuri, Muhammad; Risdiyanti, Arie (IQTISHODUNA: Jurnal Ekonomi Islam, 2022)
This paper aims to examine the Muslim community responses about Halal policy in Indonesia, especially for micro, small, and medium enterprises or known as UMKM in articulating Halal certification socially on their business products. The study becomes interesting since normatively Halal product policy is predicted to provide great opportunities for the community, including for UMKM. However, various responses occur in the community to this policy. Thus, Halal policy in its products has not been implemented optimally, especially for small and medium entrepreneurs. On the other hand, it seems more profitable for high-end entrepreneurs because they have better resources than small entrepreneurs. By using the phenomenological method, the study looks at how Muslim entrepreneurs respond to this policy in an emic perspective. It can be concluded that the community's response to the halal policy is categorized into four dilemma models; 1. Public awareness, especially entrepreneur on JPH regulations is still lacking. So, the willingness to conduct Halal certification for their products is also low 2. The cost of Halal products is considered quite burdensome. Although, the government holds a free financing program, the quota is limited and uneven. 3. Halal management chain is too bureaucratic and complicated. Therefore, products of UMKM seem to be administrative since they are only related to production. 4. Most UMKM have low competitiveness. In fact, many UMKM assume that Halal does not become one of the main branding in facing business competition with other global products.